The effect of 5-HTTLPR and a serotonergic multi-marker score on amygdala, prefrontal and anterior cingulate cortex reactivity and habituation in a large, healthy fMRI cohort - Piel, Johannes; Tost, Heike; Witt, Stephanie; Rietschel, Marcella; Meyer-Lindenberg, Andreas (European neuropsychopharmacology, 2018)
Major depressive disorder (MDD) is characterized by low mood for at least two weeks. Impaired emotion regulation has been suggested to be the consequence of dysfunctional serotonergic regulation of limbic and prefrontal regions, especially the amygdala, the anterior cingulate cortex (ACC) and the prefrontal cortex (PFC). The impact of genetic variation on brain function can be investigated with intermediate phenotypes. A suggested intermediate phenotype of MDD is emotion recognition: The 5-HTTLPR polymorphism of SLC6A4 as well as other serotonergic genes have been associated with amygdala and prefrontal function during emotion recognition. Previously, it has been suggested that habituation is a more reliable index of emotion recognition than functional activation. We examined the relationship of genes involved in serotonergic signaling with amygdala as well as prefrontal functional activation and habituation during an emotion recognition task in 171 healthy subjects. While effects of 5-HTTLPR and of a serotonergic multi-marker score (5-HTTLPR, TPH1(rs1800532), TPH2(rs4570625), HTR1A(rs6295) and HTR2A(rs6311)) on amygdala activation did not withstand correction for multiple regions of interest, we observed a strong correlation of the multi-marker score and habituation in the amygdala, DLPFC, and ACC. We replicated a well-studied intermediate phenotype for association with 5-HTTLPR and provided additional evidence for polygenic involvement. Furthermore, we showed that task habituation may be influenced by genetic variation in serotonergic signaling, particularly by a serotonergic multi-marker score. We provided preliminary evidence that PFC activation is an important intermediate phenotype of MDD. Future studies are needed to corroborate the results in larger samples.
Gesehen am 21.07.2020